Answer:
467.892
Step-by-step explanation:
467.4+0.492 =467.892
Answer:
C.Infinitely many solutions
I solved by substitution
![2x+3y=12\\-3y-3y\\2x=-3y+12\\\frac{2x=-3y+12}{2} \\x=-\frac{3}{2} y+6](https://tex.z-dn.net/?f=2x%2B3y%3D12%5C%5C-3y-3y%5C%5C2x%3D-3y%2B12%5C%5C%5Cfrac%7B2x%3D-3y%2B12%7D%7B2%7D%20%5C%5Cx%3D-%5Cfrac%7B3%7D%7B2%7D%20y%2B6)
Infinitely many solutions
Expanding the given expressions using Foil:
1)(–7x + 4)(–7x + 4) =![7x^{2}-28x-28x+16=49x^{2}-56x+16](https://tex.z-dn.net/?f=7x%5E%7B2%7D-28x-28x%2B16%3D49x%5E%7B2%7D-56x%2B16)
2) (–7x + 4)(4 – 7x)=![-28x+49x^{2}+16-28x=49x^{2}-56x+16.](https://tex.z-dn.net/?f=-28x%2B49x%5E%7B2%7D%2B16-28x%3D49x%5E%7B2%7D-56x%2B16.)
3)(–7x + 4)(–7x – 4)=
=![49x^{2}-16.](https://tex.z-dn.net/?f=49x%5E%7B2%7D-16.)
4)(–7x + 4)(7x – 4)=![49x^{2}+28x+28x-16=49x^{2}+56x-16.](https://tex.z-dn.net/?f=49x%5E%7B2%7D%2B28x%2B28x-16%3D49x%5E%7B2%7D%2B56x-16.)
The third option that is (–7x + 4)(–7x – 4) is difference of two squares.
Write out the governing equation:
y = kx.
Take any point from the given table. You haven't shared the table, so I will invent a point: (2, 9).
Then find k: k = 9/2 Then the equation becomes y = (9/2)x.
Now let x = 7 and find y: y = (9/2)(7) = 63/2
Answer: y = 63/2
Thanks so sorry to bother y’all yesterday but we are doing well and we are going out tomorrow morning to get our stuff done for tomorrow evening thanks for the call and I let him go to work tomorrow or tomorrow morning I can meet with him and meet him and there are we going out tomorrow at 7pm is that we can do that and if so I will let ya guys out tomorrow and I